A Low-cost Housing Solution: Earth Block Catenary Vaults. (August 2018) - Gohnert, Mitchell; Bulovic, Ivanka; Bradley, Ryan
Abstract: The United Nations currently estimate that 860 million people live in slums, which is 12% of the world's population. The issue is usually focussed on a lack of funds, with individuals and governments. Thus, a need to develop low-cost housing alternatives is apparent, to make housing more affordable to the poor. The project described in this paper is the design of a low-cost home, that incorporates sustainable materials and shell vaults. The materials used to construct the home are cement stabilized earth blocks (CSEB), and blocks constructed of recycled building rubble. The walls of the home are dry-stacked (no mortar), to reduce material cost and enable rapid construction. The roof of the structure comprises two catenary shaped arches, which eliminate the need of roofing materials and doubles the living space. The design of the arches is given in detail, using a segmental equilibrium method of analysis. The segmental equilibrium method predicts the thrust-line for different combinations of loads, which are kept within the middle third of the vault walls. Various other aspects of the design are also described, such as the foundations, floor slab and the support system at the base of the arch.